The effect of volatile oil mixtures on the performance and ilio-caecal microflora of broiler chickens. Issue 6 (1st November 2016) - Cetin, E.; Yibar, A.; Yesilbag, D.; Cetin, I.; Cengiz, S. S.
Abstract: The aim of this study was to investigate the individual and combined effects of rosemary, oregano and fennel volatile oil (FVO) supplementation on the performance and ilio-caecal bacteriological flora of broiler chickens. A total of 800 male Ross-308 broiler chickens were divided equally into 8 groups; each contained 100 chickens. The study included a control treatment (NC) with no dietary additives that was supplemented with oils according to the following 7 treatments: 200 mg α-tocopherol acetate/kg (PC), 100 mg oregano volatile oil (OVO)/kg, 100 mg rosemary volatile oil (RVO)/kg, 100 mg FVO/kg and an equal mixture of oregano+rosemary+fennel VO (100, 200, 400 mg/kg, VOM-1, VOM-2 and VOM-3, respectively). The experiment lasted for 6 weeks. At the end of the experiment, dietary supplementation with α-tocopherol, oregano, rosemary and FVO and two different volatile oil mixtures (VOMs) (VOM-2; VOM-3) significantly increased the body weights (BWs) of broilers at 7, 14 and 21 d of age compared to the negative control (NC) (−) and VOM-1 groups. At 0–42 d, birds fed on VOM-3 were considerably heavier and also gained more weight than NC (−) and VOM-1 groups. The blend of VOs at 400 mg/kg significantly increased Lactobacillus spp. in faeces. The blends of oregano, rosemary and FVOs (VOM-3) at 400 mg/kg concentration and also VOM-3 group exhibited stronger antibacterial activity against coliform bacteria compared to the NC (−) group. In conclusion, the blend of oregano, rosemary and fennel VOs at higher concentrations (400 mg/kg concentration) in diets can be used to stimulate the growth and can improve the intestinal microbial balance (including a reduction of coliform bacteria and an increase in Lactobacillus spp. counts) of broiler chickens.